Pengaruh cyclone dan peletakannya terhadap karakteristik gasifikasi dengan menggunakan filter zeolit alam - Ikhwahyudin, Afrizal; Ridhuan, Kemas; Nugroho, Eko (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2021)
The gas product from the gasification process contains tar content that is not thermally appropriately degraded before it leaves the reactor; for efficiency, the gasification process must go through filtering or separation using filters and cyclones. This process is essential because of the increase in the gas producer's energy density through the syn-gas filtering and purification process or syn-gas combustion. This study aimed to determine the effect of the cyclone and its placement on the combustion characteristics of gasification using natural zeolite filters, the length of time for the product gas, and how much cyclones and filters can separate tar in updraft type gasification process. In this study, the gasification process uses an updraft type reactor, biomass fuel using rubberwood, filters using natural zeolite media, and adding a coolant (condenser). Testing by varying the addition and placement of the cyclone position. The test results show that the use of cyclone variations does not affect the Temperatur in the reactor. A cyclone's effect using a natural zeolite filter on the characteristics of the combustion product (flame) is very large; namely, the color of the fire is bluish and clean with little smoke and the size of the flame coming out of the burner. The effect of a series of cyclones and natural zeolite filters on the flame duration of Syn-Gas on the burner is ± 44 minutes. Without using the cyclone series, the flame time in the burner only reaches ± 28 minutes. The tar that can be separated by the burner and filter without using a cyclone is 381 grams, and the tar that is separated by the cyclone in the cyclone series after the condenser can accommodate as much as 450 grams.